Adaptive Robust Turbo Equalization for Power-Line Communications - Chuah, Teong Chee (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
Data communication over power lines requires advanced signal-processing techniques to cope with time-varying intersymbol interference and severe impulsive noise. A further challenge comes from strict regulatory constraints that stipulate low transmission power. In this paper, we propose an adaptive robust turbo equalizer for single-carrier coded systems. The turbo equalizer has a component equalizer to deal with the deep frequency notches present in power-line channels. The component equalizer' exchanges extrinsic information with a component decoder to perform iterative detection. To facilitate adaptive equalization in time-varying power-line channels, a simple system identification-based channel estimator is incorporated. Most important, a nonlinear-matched myriad filter (MMyF) is used for efficient baseband filtering in impulsive channels. The results show that the MMyF is indispensable for the turbo equalizer to achieve reliable channel estimation and data detection in impulsive power lines. Substantial performance improvements over the conventional scheme designed for Gaussian channels are observed.